Prevalence of oropharyngeal antibiotic‐resistant flora among residents of aged care facilities: a pilot study. Issue 7 (4th May 2015) - Etherton‐Beer, Christopher D.; Inglis, Tim; Waterer, Grant
<x xml:space="preserve">Abstract</x> Residents in 11 long‐term care facilities, and presenting to a single tertiary hospital site, were sampled to estimate prevalence of oropharyngeal colonization with resistant Gram‐negative bacteria. From 124 residents, only one isolate (0.8%; 95% confidence interval 0.0%, 4.4) was multi‐resistant (an extended‐spectrum β‐lactamase producing Escherichia coli) indicating that different treatment recommendations for respiratory infections in this population may not be justified.